Aneka Ragam Spiritualitas dalam Kebudayaan Kontemporer - Naim, Ngainun (el Harakah: Jurnal Budaya Islam, 2009)
Spiritualism is an inseparable part of human existence. The reduction of this dimension will effect negatively for human existence. This causes the emergence of new phenomenon, or even culture, in the life of modern society. The phenomenon is the increase of their interest in spiritualism. Even though, spiritualism in this context is not always identical with religion. Even, this phenomenon cannot be separated from capitalism. Therefore, the spiritualism that develops recently has various forms, that is, (1) Spiritualism Secularization, (2) Spiritualism Immanence, (3) Spiritualism Libidinalisation, (4) Schizo-spiritualism, (5) Hybrid-spiritualism, and (6) Techno-spiritualism. Furthermore, there is also another expression of spiritualism, that is, the emergence of new religion or quasi-religion movement. The emergence of this movement is influenced by the effort to release from religious countercultures. Other manifestation of this spiritualism is in the form of fundamentalism movement. In extreme point, this movement can be seen from the emergence of extreme cult, such as those that teach tragic way of death. Spiritualisme adalah bagian tak terpisahkan dari eksistensi manusia. Pengurangan dimensi ini akan berdampak negatif bagi eksistensi manusia. Hal ini menyebabkan munculnya fenomena baru, atau bahkan budaya baru dalam kehidupan masyarakat modern. Fenomena ini termasuk meningkatnya minat mereka terhadap spiritualisme. Meski demikian, spiritualisme dalam konteks ini tidak selalu identik dengan agama. Bahkan, fenomena ini tak lepas dari kapitalisme. Oleh karena itu, spiritualitas yang berkembang baru-baru ini memiliki berbagai bentuk, yaitu (1) spiritualisme sekularisasi, (2) spiritualisme iman, (3) spiritualisme libidinalisasi, (4) schizo-spiritualisme, (5) hybrid-spiritualism, dan (6) techno-spiritualisme. Selanjutnya, ada pula ekspresi spiritualisme lain, yaitu munculnya agama baru atau gerakan kuasi-agama. Munculnya gerakan ini dipengaruhi oleh usaha melepaskan diri dari perhelatan religius. Manifestasi lain dari spiritualisme ini adalah dalam bentuk gerakan fundamentalisme. Intinya, gerakan ini bisa dilihat dari kemunculan kultus ekstrem, seperti yang mengajarkan cara tragis kematian.